Inventarisasi Dan Pemanfaatan Jenis Tumbuhan Invasif di Perumahan Bumi Panyileukan Kota Bandung - Alika Maulidina Rahma; Fani Wilma Mulyana; Rahmat Taufik Mustahiq Akbar (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The presence of invasive plants can often threaten biodiversity, affect the availability of natural resources, and even disrupt the balance of the ecosystem. In a residential context, in-depth knowledge of invasive plant species is important to identify risks and potential impacts on the environment and consider the possibility of their positive use. Therefore, this study aims to find out data on invasive plant types in this housing complex. The method in this research combines qualitative and quantitative descriptive approaches. A qualitative descriptive approach was used to gain an in-depth understanding of the characteristics, distribution and interactions of invasive plants in the Bumi Panyileukan Housing Complex. Meanwhile, a quantitative approach was applied in data analysis to measure a number of variables related to the identified invasive plants. The observation method in the form of sampling invasive plants is used as a basis for collecting focused and representative data on plant types in the residential environment. It is hoped that the integration of these methods can provide a comprehensive picture of invasive plant species and their characteristics in the context of Bumi Panyileukan Housing in Bandung City. The location was chosen deliberately, namely around 16% of the total area. The results obtained were 31 families of 60 invasive plant species. The highest families are in the Araceae and Euphorbiaceae families with a percentage of up to 26% in this area. There are 58 species of plants introduced from outside Indonesia and two species are native to Indonesia. Most plants are used as ornamental plants and some are wild invasive plants which can threaten the balance of the ecosystem so comprehensive control needs to be carried out